Nutritional quality: Populations characterized during 2023 in forage breeding program. - Jauregui, Rosa; Mazabel, Johanna; Hernández, Luis Miguel (International Center for Tropical Agriculture, 2023)
The objective of this report is to outline the assessment of the nutritional quality within the hybrid breeding program across various sampling periods throughout the year. The parameters being examined encompass Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Crude Protein (CP), and In Vitro Dry Matter Digestibility (IVDDM). In the year 2023, the evaluation focused on the following populations: Urochloa humidicola Bh16b hybrids, Urochloa humidicola Bh22 hybrids, Urochloa interspecific Era trial, and Panicum maximum PM21. The results obtained will contribute to the strategic selection of the forage breeding program, offering valuable guidance to identify hybrids that exhibit superior nutritional value throughout different sampling.